Evaluación química y biológica de la fertilidad del suelo en los sistemas agroforestales con café de los sectores Consapamba y Pueblo Nuevo de los cantones Espindola y Loja. - Zambrano Sarango, Paola Lourdes (2019)
In Loja province, coffee is one of the most important products grown and is known nationally and internationally for its quality and aroma. The deterioration of the productive capacity of the soils and the consequent decrease in yields affect the economy of coffee farmers who, in their eagerness to reverse this situation, seek to restore the availability of nutrients in the soil through the use of fertilizers recommended by commercial houses, without considering nutrient availability and crop requirements. The modified Olsen extractor solution, officially used in the country by the Soil Laboratories Network of Ecuador to determine the content of the element that can be used for the plant, evaluated the contents of N, P, K, S, Mg, Zn, Mn, Cu, Fe and B, to perform a comparative analysis, in order to generate a fertilization plan. In the SAF with coffee from Consapamba the physical conditions of the soil were placed in the category of very poor; the practically neutral pHH2O, the low cation exchange capacity, the P, Zn, Mn, B and Fe did not correspond between the weight of the dry matter of the biological evaluation with the concentration of the available nutrient of the chemical analysis for any element, the most deficient elements are N, S, P. In the SAF with coffee from Pueblo Nuevo, the physical conditions of the soil were placed in the category of poor; the acidic pHH2O, the low cation exchange capacity, the N, P, K, Mg, Zn, Mn and B did not correspond between the weight of the dry matter of the biological evaluation with the concentration of the available nutrient of the chemical analysis, the most deficient elements are P, N, S, Mg, K and B. Keywords: biological evaluation, extractant solution, nutritional solutions, indicator plant, correspondence.